Reinkejev edem glasilk - Kravos, Alenka (Zdravniški vestnik, 2010)
Background. Reinke''s edema is one of the most frequent head and neck diseases. A great majority of the patients are middle-aged women. In the initial stage of the disease, a deeper voice appears. Hoarseness is a sign of an advanced disease. An enormous edema can even cause breathing poblems. The known etiologic factors for the development of Reinke''s edema are smoking, gastroesophageal reflux, vocal overuse, unfavourable microclimate at work and possibly thyroid disfunction and allergy. Besides the causal treatment, in a majority of patients the surgical treatment is the only possibility of cure. The voice therapy after the surgical procedure helps the patient to regain a proper vocal technique and vocal habits. Conclusions. Reinke''s edema is quite a frequent cause of voice disorders. In order to treat the disease and preventa recurrence, all etiological factors must be detected and eliminated or extenuated. A proper voice therapy that follows the surgical treatment can enable the patient to regain a good voice quality.
Keywords: Etiologija; etiology; Glasilke; Grlo, edem; Laryngeal Edema; Reinkejev edem; therapy; Vocal Cords; Zdravljenje